Implementation of Web-Assisted Project Based Learning Model Learning to Improve Critical Thinking Skills and Science Process Skills - Kause, Migdes Christianto; Sutarto, Joko; Kustiono, Kustiono (FKIP Universitas Lampung, 2022)
The purpose of this study was to describe and analyze the effectiveness of the website-based Project Based Learning approach to improving students' critical thinking skills and science process skills. The design of this study was a quasi-experimental with a nonequivalent control group design in which the experimental and control groups were selected randomly. The instruments used to measure critical thinking skills are test questions while the instruments used to measure science process skills are test questions and observation sheets. The results of the study show that learning before and after Project Based e-Learning has increased by 9.8%. The increase in students' critical thinking skills is caused by the use of Project Based Learning where this model can make students play an active role in solving problems, making decisions, researching, presenting and creating documents. The application of Project Based eLearning to class V science material has experienced a significant increase. This is shown by the results of hypothesis testing where the sig (2-tailed) value is 0.00 (p <0.05). The increase in science process skills occurs because Project-Based learning can support participants in developing their creativity in designing and creating projects that can be used to solve problems. Keywords: project based learning, critical thinking skills, science process skills. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1598-1609